Diagnostic Test Validity of MCV for Determination of Thalassaemia Carrier in Bangladesh - Haque, Nazmul; Saha, Narayan Chandra; Rahman, Mohammad Ekhlasur; Ahmed, Tahmina (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Mean corpuscular volume (MCV) and mean corpuscular haemoglobin (MCH) of red blood cell is the useful diagnostic test which is performed during routine blood examination. Objective: The purpose of the present study was to measure the diagnostic test validity of MCV for the determination of thalassaemia carrier. Methodology: This analytic cross-sectional study was carried out in the Department of Pediatrics and Department of Medicine at MAG Osmani Medical College Hospital, Sylhet, Bangladesh from September 2007 to January 2009 for a period of one year and five months. Siblings and cousins of beta Thalassemia major and Hb- E -beta Thalassemia satisfying the selection criteria were enrolled. The detailed history and thorough physical examination were done meticulously. Five (5) mL blood was drawn from each case and control for determination of MCV and Hb-Electrophoresis. Result: Total 63 were enrolled as cases and total 65 were enrolled as controls. Sensitivity, specificity, positive and negative predictive value of MCV in determination of thalassemic carriers were 92%, 89.2%, 89.2% and 92% respectively. The area under the curve value was 0.094 (0.035 to 0.152). Conclusion: In conclusion the diagnostic test validity of MCH and MCH is high in determination of Thalassemic carrier. Journal of National Institute of Neurosciences Bangladesh, 2016;2(2): 94-97]